Doctoral research, COVID-19, and political crisis in Ethiopia, Sudan, Rwanda, and the UK: challenges, responses, and recommendations [version 1; peer review: 2 approved] - Corinna Thellmann; Jean Paul Bikorimana; Dereje Wonde; Tseganesh Mulugeta; Badraldeen Ali Bashir Alnoor Ahmed; Addisu Tsegaye; Jeffrey Pocock; Ursin Bayisenge (NIHR Open Research, 2023)
Background Conducting doctoral research is a challenging endeavour, a challenge which as the growing literature on the subject has shown, the COVD-19 pandemic has made even more so. For some doctoral researchers, however, the pandemic has also been accompanied by political unrest and military conflict, putting them and their networks at risk and making their research especially difficult to sustain. Methods We have used a collaborative auto-ethnography, and we, a group of seven doctoral researchers based in Ethiopia, Rwanda, Sudan and UK have written our experiences. Results Drawing upon the results of a collaborative auto-ethnography (CAE), this article records and discusses the experiences of a group of doctoral researchers who with the support of their organisation, the Social Science for Severe Stigmatised Skin Diseases (5S) Foundation, have been attempting to cope with both the pandemic and internal instability and strife. After firstly setting the context, the article explains why for the purposes of this paper CAE was adopted as our method, and then documents and discusses the experiences of seven doctoral researchers based in Ethiopia, Sudan, Rwanda, and the UK, doing so in terms of four different themes: New Ways of Working and Its Impact, Change and Delay, Mental Health and Well-Being Impact, and Qualities and Capacities. Conclusion What these experiences tell us is that this group of doctoral researchers have found themselves in extremely challenging situations, which have placed exceptionally high demands on them and their support networks, and this has had an impact on their health and well-being although also been the catalyst for some more positive development. Given their lived experiences, the article finishes with a series of recommendations for future research projects of this kind.